Foreign economic policy of Georgia since gaining the Independence. Georgische Aussenwirtschaftspolitik nach der Gewinnung der Unabhängigkeit - Irina Gogorishvili (Eesti Majanduspoliitilised Väitlused, 2016)
The paper gives the description and study of the foreign economic policy of Georgia in the during independence period. The purpose of the study is to describe and analyze the preconditions for the sustainable and stable development of the country by means developing foreign trade, improving investment potential and using an efficient foreign debt management system. During the studies, the paper used the materials of the studies conducted by Georgian and foreign scientists, as well as international and private organizations and their evaluations. The opinions about the improvement and risks of the present-day situation are given following the consideration of different components of the foreign economic policy of Georgia, and opportunities for the rationalization of foreign policy of Georgia are offered.